Antifouling activity of portimine, select semisynthetic analogues, and other microalga-derived spirocyclic imines. Issue 8 (14th September 2018) - Brooke, Darby G.; Cervin, Gunnar; Champeau, Olivier; Harwood, D. Tim; Pavia, Henrik; Selwood, Andrew I.; Svenson, Johan; Tremblay, Louis A.; Cahill, Patrick L.
Abstract: A range of natural products from marine invertebrates, bacteria and fungi have been assessed as leads for nature-inspired antifouling (AF) biocides, but little attention has been paid to microalgal-derived compounds. This study assessed the AF activity of the spirocyclic imine portimine (1 ), which is produced by the benthic mat-forming dinoflagellate Vulcanodinium rugosum . Portimine displayed potent AF activity in a panel of four macrofouling bioassays (EC50 0.06–62.5 ng ml −1 ), and this activity was distinct from that of the related compounds gymnodimine-A (2 ), 13-desmethyl spirolide C (3 ), and pinnatoxin-F (4 ). The proposed mechanism of action for portimine is induction of apoptosis, based on the observation that portimine inhibited macrofouling organisms at developmental stages known to involve apoptotic processes. Semisynthetic modification of select portions of the portimine molecule was subsequently undertaken. Observed changes in bioactivity of the resulting semisynthetic analogues of portimine were consistent with portimine's unprecedented 5-membered imine ring structure playing a central role in its AF activity.